Produção de sementes de mamona no sul do Rio Grande do Sul - Eicholz, Eberson Diedrich (2009)
The success of any agricultural business based in commercial exploitation of plant crops requires the use of high quality seeds, with potential to grow vigorous and high yielding plants in a short period of time. Regarding to castor bean, there are few articles related to seed production in Rio Grande do Sul. This work aimed to study the seed production viability in southern of Rio Grande do Sul. There were carried out experiments in two farms, season of 2006/07, in Canguçu, using IAC 80 and AL Guarany 2002 cultivars, sowed in two different dates (November and December). It was evaluated the agronomic performance of plants in the field and yield components, as well as the physiological and physic quality of seeds from different parts of raceme (divided in three parts) and different raceme-orders. These analyses were conducted at Embrapa Clima Temperado, Pelotas/RS. According to the results, it was observed genotype x environment interaction effects on the yield components and physiological and physic quality of seeds in AL Guarany 2002 e IAC 80 cultivars, considering that the first raceme-order seed position doesn t affect the seeds physiological and physic quality. In AL Guarany 2002 , the seeds from the first and second raceme-order presented quality, with no environment or sowing date influence, meanwhile IAC 80 cultivar showed quality in November sowing, with no environment influence. It is concluded that it is possible to produce seeds with physiological and physic quality of castor bean in southern of Rio Grande do Sul.